War in world history society, technology, and war from ancient times to the present - Morillo, Stephen
Designed for use at the college level as a textbook for military history courses or supplemental reading for world history courses, this text offers an introduction and original synthesis of global military history. Each chapter traces key developments in military institutions and practices set in three crucial contexts: politics and institutions; social structures and economics; and cultures. Primary sources throughout the text give students a look at the writings historians use to draw conclusions, while Issue Boxes raise and explore historiographical controversies in military history. A two-volume format follows the usual division of world and western civilization courses and allows a standard semester split of military history survey courses. Volume One covers 2000 BC through 1500 AD. Volume Two covers the dawn of global warfare in 1500 through the present.